A high‐efficiency global model of optimization design of impervious surfaces for alleviating urban waterlogging in urban renewal. Issue 4 (5th May 2021) - Yu, Huafei; Zhao, Yaolong; Xu, Tao; Li, Jiufeng; Tang, Xianzhe; Wang, Fangfang; Fu, Yingchun
Abstract: The rapid expansion and unreasonable design of impervious surfaces caused by urbanization have seriously aggravated urban waterlogging. Determining how to optimize the spatial layout of impervious surfaces is the focus of urban waterlogging prevention in urban renewal. The existing urban‐renewal methods include constructing low‐impact development measures by reducing the area of impervious surfaces or implementing a local high‐strength design based on the ant colony algorithm (ACA) from the viewpoint of optimization design. However, these methods have obvious shortcomings in terms of time efficiency, and their optimized design schemes are insufficient at considering the global impervious surface design. Therefore, to address these problems, the study proposes a coupled model of multivariate linear programming and Soil Conservation Service curve number. The model is employed in the central city of Guangzhou, China. The results show, first, that the optimal design of impervious surfaces in urban renewal is to construct a discontinuous connection of high‐low‐high‐density impervious surfaces; second, that, compared with ACA, our method has higher robustness, increases the average optimization rate by 4.48 to 14.00%, and reduces the optimization time over 30 days to 20.8 s; and third, that the optimal results realize the global low‐strength transformation as complements of the existing design scheme of local high‐strength transformation. This study optimizes methods for alleviating urban waterlogging urban renewal at different scales or intensities.